Estudo da aplicação de superfícies seletivas em frequência em ambientes indoor - Almeida, Milena Bezerra de (Universidade Federal Rural do Semi-Árido, 2019)
In the present work is proposed a study about the application of a frequency selective on single-band surface that filters the 2.45 GHz signal according to the standard Institute of Electrical and Electronic Engineers (IEEE) 802.11 in an indoor environment. In this perspective, it was made the electrical characterization in 20 samples of civil construction materials in order to explore the electrical permissiveness of these materials, and thus investigate the behavior of a selective surface in frequency with conductor patch which acts as a reject-band filter on these samples. The electrical characterization of the materials was done through the coaxial line method in a frequency range of 1 to 10 GHz, in this way, the permittivity values were extracted at the desired frequency. At these values, the frequency selective surfaces were simulated for a sample of each type of material, in view of this the results for the transmission coefficient with respect to frequency were achieved using the ANSOFT HFSS software. The results obtained by the simulations it’s possible check the behavior in reject-band filter with width single-band in all samples.
Monografia
Keywords: Superfície Seletiva em Frequência; Caracterização elétrica; Permissividade elétrica; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA